Combining Earliest Deadline First Scheduling with Scheduled Traffic Support in Automotive TSN-Based Networks - Luca Leonardi; Lucia Lo Bello; Gaetano Patti (Applied System Innovation, 2022)
Recent work on automotive communications based on the Time-Sensitive Networking (TSN) standards proposed an approach to handle all the real-time frames in a uniform way regardless of their arrival pattern. According to such an approach, instead of binding all the frames of the same flow to a traffic class, each periodic or event-driven frame is scheduled based on its absolute deadline according to the Earliest Deadline First (EDF) algorithm. The approach does not impose additional frame overhead and does not require complex offline configurations that would be unsuitable for event-driven traffic. However, EDF scheduling cannot support time-driven communications. To solve this problem, this paper proposes a framework that combines the flexibility of online EDF frame scheduling for both periodic and event-driven traffic with the ability to guarantee temporal isolation to time-driven traffic. The paper describes the design of the proposed approach and the performance obtained using the OMNeT++ simulation environment.